2006
DOI: 10.1007/s00020-006-1430-8
|View full text |Cite
|
Sign up to set email alerts
|

The C*-envelope of the Tensor Algebra of a Directed Graph

Abstract: Abstract. Given an arbitrary countable directed graph G we prove the C * -envelope of the tensor algebra T + (G) coincides with the universal Cuntz-Krieger algebra associated with G. Our approach is concrete in nature and does not rely on Hilbert module machinery. We show how our results extend to the case of higher rank graphs, where an analogous result is obtained for the tensor algebra of a row-finite k-graph with no sources. IntroductionThe fundamental nonselfadjoint operator algebra associated with a coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In fact, we have shown that Szymanski's Theorem is not necessary and that one can obtain Theorem 7.7 by using the more elementary "gauge-invariant uniqueness theorem" [21].…”
Section: Acknowledgementsmentioning
confidence: 98%
“…In fact, we have shown that Szymanski's Theorem is not necessary and that one can obtain Theorem 7.7 by using the more elementary "gauge-invariant uniqueness theorem" [21].…”
Section: Acknowledgementsmentioning
confidence: 98%
“…Consequently the associated Cuntz-Pimsner algebra O(E) is nuclear [26,Corollary 7.5]. By a result of Katsoulis and Kribs [23], O(E) is the C*-envelope of T + (E).…”
Section: Dilation and The Semi-crossed Productmentioning
confidence: 99%
“…We now obtain one of the main results of [7] as a corollary. Note that in [7], the proof of the above corollary is essentially self-contained and avoids the heavy machinery used in this paper.…”
Section: Lemma 32 If X Be a Faithful C * -Correspondence Over A Thenmentioning
confidence: 90%
“…In the special case of a graph correspondence, this was done in [7] with the help of a wellknown process called "adding tails to a graph." This process has been generalized to arbitrary correspondences by Muhly and Tomforde [12].…”
Section: Lemma 32 If X Be a Faithful C * -Correspondence Over A Thenmentioning
confidence: 99%
See 1 more Smart Citation